Comparison of accelerated CXL alone, accelerated CXL-ICRS, and accelerated CXL-TG-PRK in progressive keratoconus and other corneal ectasias. Issue 2 (February 2020) - Singal, Neera; Ong Tone, Stephan; Stein, Raymond; Bujak, Matthew C.; Chan, Clara C.; Chew, Hall F.; El-Defrawy, Sherif; Jin, Yaping; Kranemann, Christoph; Rabinovitch, Theodore; Rootman, David S.; Slomovic, Allan R.; et al.
Abstract : Corneal crosslinking, CXL with intrastromal corneal ring segments, and CXL with topography-guided photorefractive keratectomy showed improvement in visual and topographical outcomes in patients with corneal ectasias 1 year postoperatively. Abstract : Purpose: To compare accelerated corneal crosslinking (CXL) alone, CXL with simultaneous intrastromal corneal ring segments (CXL-ICRS), and CXL with simultaneous topography-guided photorefractive keratectomy (CXL-TG-PRK) in progressive keratoconus, pellucid marginal degeneration (PMD), or laser in situ keratomileusis (LASIK)-induced ectasia. Setting: The Kensington Eye Institute and Bochner Eye Institute, Toronto, Canada. Design: Prospective nonrandomized interventional study. Methods: Visual and topographical outcomes using a comparative analysis adjusting for preoperative maximum keratometry (Kmax) were evaluated 1 year postoperatively. Results: Four hundred fifty-two eyes from 375 patients with progressive keratoconus, PMD, or LASIK-induced ectasia that underwent accelerated (9 mW/cm 2, 10 minutes) CXL alone (n = 204), CXL-ICRS (n = 126), or CXL-TG-PRK (n = 122) were included. Change in logarithm of the minimum angle of resolution uncorrected distance visual acuity was significant with CXL-ICRS (−0.31; 95% CI, −0.38 to −0.24) and CXL-TG-PRK (−0.16; 95% CI, −0.24 to −0.09), but not with CXL alone. No significant differences in change were found between the 3 groups. Change in corrected distance visual acuity (CDVA) was significant in all 3 groups: −0.12 (95% CI, −0.15 to −0.10) with CXL alone, −0.23 (95% CI, −0.27 to −0.20) with CXL-ICRS, and −0.17 (95% CI, −0.21 to −0.13) with CXL-TG-PRK. Improvement in CDVA was greater with CXL-ICRS than with CXL alone (−0.08 ± 0.02; P < .0001) and CXL-TG-PRK (−0.05 ± 0.02; P = .005). Change in Kmax was significant with CXL-ICRS [−3.21 diopters (D); 95% CI, −3.98 to −2.45] and CXL-TG-PRK (−3.69 D; 95% CI, −4.49 to −2.90), but not with CXL alone (−0.05 D; 95% CI, −0.66 to 0.55). Conclusions: CXL alone might be best for keratoconic patients who meet the inclusion criteria. CXL-ICRS might be more effective for eyes with more irregular astigmatism and worse CDVA and CXL-TG-PRK for eyes requiring improvements in irregular astigmatism but still have good CDVA.